Study of cognitive impairment and suspected dementia in geriatric population and its association with socio-demographic factors in urban slum area of metropolitan city - Kolte, Darshana; Shelke, Pallavi; Rajput, Rupali R. (International Journal Of Community Medicine And Public Health, 2018)
Background: According to the World Health Organization (WHO) Mental Health Report 2001, by the year 2025, elderly population will make up for more than 20% of the total world population.Literature suggests that the prevalence of dementia in geriatric population is 1% at the age of 60-64 years and it doubles every five years thereafter. Thus prevalence is 30-40% at the age of 85 and above. Methods: The present study was carried out in Kumbharwada Health Post area in Dharavi slums in Mumbai. The study was community based descriptive study with cross sectional design. The period of study was from January 2005 to June 2006. Results: It was observed that 25.6% of the respondents were from 60-64 years of age, 28.9% were from 65 to 69 years of age. The distribution of respondents according to the cognitive status as defined by Hindi mental state examination (HMSE) was found as, 77.3% of the respondents have no cognitive impairment. Prevalence of mild cognitive impairment and suspected dementia was 18.6% and 4.1% respectively. Conclusions: Prevalence of cognitive impairment and suspected dementia was found to be 18.6% and 4.1% respectively. There was no difference in the cognitive status of male and female. More than half of the respondents were from 60-69 years of age. Mean age of the respondents was 68.9 years. Proportion of females in each age group was approximately two-thirds of the total; almost three forth of them were widowed.